Research of the Test Bench and Method of Integrated Electric Drive Axle for Light Commercial Vehicle - Rui Zhan; Huaguo Cheng; Kang Xu; Jiyong Jia (Jixie chuandong)
Aiming at the test requirements of integrated electric drive axle for light commercial vehicle， the test bench of integrated electric drive axle for light commercial vehicle is designed. The test methods suit for integrated electronic drive axle are established refer to traditional drive axle and electric motor test methods. By using the developed test bench and established test method， the performance and fatigue tests of the integrated electric drive axle are finished. It provides test technology support for design and manufacture departments.